A relação entre a teoria física e o desejo na filosofia política de Hobbes - SILVA, Maria de Lourdes (2009)
This dissertation tries to show the relationship between the physical and the political theories of Thomas Hobbes. This is possible because Hobbes made no distinction between the way in which physical bodies and humans move: every body moves as a result of the action of another body. When a body is affected by another, movements or conatus appear within itself that can manifest externally, determining its trajectory. In man, those conatus appear in the form of sentiments: desire or aversion. The conatus desire or aversion unchain other passions such as fear, courage, hope, despair etc. However, it is those conatus that play the role of determining choices and human behavior. Given the force of those passions, the State has to exert the tremendous power that Hobbes allows to the sovereign. This dissertation will try to make those relationships clear